Functional Asymmetry of Human Prefrontal Cortex: Encoding and Retrieval of Verbally and Nonverbally Coded Information - Opitz, Bertram; Mecklinger, Axel; Friederici, Angela D. (Learning & memory (Cold Spring Harbor, N.Y.), 2000)
There are several views about the organization of memory functions in the human prefrontal cortex. One view assumes a process-specific brain lateralization according to different memory subprocesses, that is, encoding and retrieval. An alternative view emphasizes content-specific lateralization of brain systems involved in memory processes. This study addresses this apparent inconsistency between process- and content-specific lateralization of brain activity by investigating the effects of verbal and nonverbal encoding on prefrontal activations during encoding and retrieval of environmental novel sounds using fMRI. An intentional memory task was applied in which subjects were required either to judge the sounds' loudness (nonverbal encoding task) or to indicate whether or not a sound can be verbally described (verbal encoding task). Retrieval processes were examined in a subsequent yes/no recognition test. In the study phase the right posterior dorsolateral prefrontal cortex (PFC) was activated in both tasks. During verbal encoding additional activation of the left dorsolateral PFC was obtained. Retrieval-related fMRI activity varied as a function of encoding task: For the nonverbal task we detected an activation focus in the right posterior dorsolateral PFC whereas an activation in the left dorsolateral PFC was observed for the verbal task. These findings indicate that the right dorsolateral PFC is engaged in encoding of auditory information irrespective of encoding task. The lateralization of PFC activity during retrieval was shown to depend on the availability of verbal codes, with left hemispheric involvement for verbally and right hemispheric activation for nonverbally coded information.